INOVASI PELAYANAN PUBLIK SEKTOR EKONOMI PADA BADAN USAHA MILIK DESA (BUMDES) CIBIRU WETAN KABUPATEN BANDUNG - Engkus; Japa, Ershabilla Ardian; Maulida, Fadhila Alma; Nugraha, Hedi Wildan; Tarisman, Iman (Universitas Djuanda, 2024)
Villages in Indonesia have the potential to improve their quality of life through public services, but they often need more access to technology and adequate infrastructure. Therefore, digital innovation is needed to solve these barriers and improve the efficiency and effectiveness of public services at the village level. This research aims to describe the public service innovation of Village-Owned Enterprises (BUMDes) in the economic sector in Cibiru Wetan Village. The research method is a descriptive qualitative approach using data collection techniques such as interviews, observation, and documentation. The informant selection technique uses a purposive sampling technique. Result of this research shows that the innovation of Village-Owned Enterprises (BUMDes) public services in the economic sector in Cibiru Wetan Village supported by digital marketing is able to increase Village Original Income (PADes) and make community empowerment more productive. This research concludes that implementing adaptive innovations supported by public service collaborations with a high spirit of initiative mostly affects the success of village programs in realizing their vision and mission so that the community welfare can improve continually.